Application of SERS active substrate prepared by nanotechnology in ophthalmic care. (30th September 2020) - Lin, Lili; Guo, Jiarui; Hao, Yang
The application of nanomaterials in ocular drug delivery is mainly concentrated in nano-controlled release systems. Due to the unique properties of nanomaterials, the use of nanomaterials to carry drugs for treating eye diseases has great advantages compared with traditional drug delivery methods. The nano-formulation of the drug has higher bioavailability and lower side effects. Therefore, the nano-controlled release system has a good application prospect in ophthalmology. In this paper, Fe2 O3 magnetic nanoparticles were first prepared by co-deposition, and then the nanoparticles were clad with silica to prepare Fe2 O3 @SiO2 core-shell nanostructures. Secondly, an ordered array surface-enhanced Raman scattering (SERS) active substrate was formed on the surface of the porous layer of porous anode aluminium oxide (PAA) and the barrier layer using vacuum electron beam evaporation technology using PAA films as templates. Then, the shell thickness of Fe2 O3 @SiO2 and the number of coated magnetic particles were controlled by controlling the dosage of ethyl orthosilicate, and a layer of SERS active gold nanoshells was grown after further adsorption of gold seeds to prepare a composite SERS active substrate. Enhanced performance magnetic nanomaterial Fe2 O3 @SiO2 @PAA @Au. Finally, the SERS spectrum and fluorescence quenching characteristics of ocular cells adsorbed on the substrate were detected and analysed. The results show that the magnetic nanomaterial Fe2 O3 @SiO2 @PAA @Au with enhanced performance of SERS active substrate has a good enhancement effect on the Raman scattering signal of eye cells, and to a certain extent, it can eliminate the interference of the fluorescent background. Moreover, the ordered array of SERS active substrates not only has a high SERS enhancement ability and ability to quench fluorescence, but also does not have interference peaks of oxalate impurities remaining in the PAA film, which can obtain more detailed information of the Raman scattering spectrum of eye cells to achieve eye care.